IMF Survey, Volume 35, Issue 14. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
Seminar on preventing crises; Country briefs: Hong Kong SAR and Brazil; France's labor market reform; Seigniorage and governance; Chinese inflation; China's monetary policy; Mekong regional integration; Scaling up aid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet